Gaya Penyutradaraan Naratif Bong Joon-Ho: Studi Kasus Film Memories of Murder (2003), The Host (2006), dan Parasite (2019) - Agustinus Dwi Nugroho; Antonius Janu Haryono (Rekam, 2026)
Bong Joon-Ho’s Narrative Directing Style: A Case Study of the Films Memories of Murder (2003), The Host (2006), and Parasite (2019). Bong Joon Ho has gained significant international recognition after winning the Best Picture category at the 2020 Academy Awards and bringing home trophies for Best International Feature Film, Best Screenplay, and Best Director for his film Parasite (2019). This achievement marked a historical milestone  because it is the first time in history that an Asian film has won the Best Picture category. This certainly brings a breath of fresh air to Asian cinema, including Indonesia. Departing from this phenomenon, this study analyzes the film form of several works directed by Bong Joon Ho, by dissecting the narrative structure and narrative as a form of his directing style. The researcher selected three film samples for analysis, namely, Memories of Murder (2003), The Host (2006), and Parasite (2019), all three of which were chosen to represent different genres and narrative forms, namely, crime-thriller science fiction, and comedy-drama. The data collection technique used is the observation method, regarding the aspects and narrative structures used, as well as the forms of the narrative. The relationship between narrative structure and narration will be examined in more depth. Its significance for film scholarship lies in expanding the body of knowledge of film forms produced by South Korean films, with their distinctive narrative forms. Bong-Joon-Ho's narrative directing style shares a common narrative, utilizing both limited and unlimited storytelling in a combined manner.